Peran Apa yang Dimainkan Digital Marketing dalam Nation Branding di Masa Perang? Konseptual Model dari Kasus Ukraina - Reztrianti, Diajeng; Usep Suhud; Setyo Ferry Wibowo (Samudra Publisher, 2025)
The present research proposes a conceptual model that explains how digital marketing communication strategies play a role in shaping nation brand equity amid geopolitical crises. This assertion is supported by a case study of the Russia-Ukraine war. The research adopts a model-based conceptual approach, integrating literature on digital narrative content, social media diplomacy and digital multichannel orchestration as key variables that influence perceived trust, emotional engagement and digital brand reputation. Utilizing Toulmin's argument framework, the research offers a logical justification for the relationship between the variables, thereby demonstrating that authentic and emotional digital narratives foster global public trust, while digital diplomacy enhances country engagement and credibility, and multichannel orchestration strengthens reputation through cross-platform message consistency. This study concludes that digital marketing communication is not merely a promotional tool, but a strategic instrument in building global perceptions during times of crisis. This research makes a theoretical contribution by expanding the scope of brand equity theory from the business context to the geopolitical realm. Furthermore, it provides a pragmatic framework for states to formulate integrated and responsive digital communication strategies in periods of conflict.